Conflict, Livelihoods and Survival among Miners and Farmers in Gweru's Greenvale, 2000–2016. (15th September 2019) - Munhenzva, Petronella Munyaradzi; Chimhete, Nathaniel; Kufakurinani, Ushehwedu
The paper analyses the interface of conflict, livelihoods and survival in a peri-urban region where mining and farming core-exist. We use the case study of Greenvale, a peri-urban area in Gweru, a city in the Midlands Region of Zimbabwe. Gweru is the fourth largest city in the country after Mutare, Bulawayo and Harare. We explore how the co-existence of mining and farming generated conflict, which delayed sustainable livelihoods and maximum benefit from the exploitation of the environment through mining and farming. The conflicts, which pitted miners against farmers, farmers against farmers and miners against miners, manifested themselves in physical violence, accusations of thefts and contestations over plots, among others. The conflicts bred uncertainty, distrust and in the process compromised on sustainable investment in the exploitation of the environment, be it through mining or farming.